Age-related modulation of the isthmic and uterine mucosal innate immune defense system in laying hens. (27th March 2019) - Elhamouly, M; Nii, T; Isobe, N; Yoshimura, Y
ABSTRACT: Sustained production of good quality eggs for longer production cycles is a challenge for poultry farms. The impact of aging on the mucosal immune defense in the isthmus and uterus of hens, where the eggshell membrane and eggshell are formed, remains obscure. Thus, the aim of this study was to determine whether aging affects the mucosal tight junction (TJ) proteins, the synthesis of antimicrobial peptides including avian β-defensins (AvBDs) and cathelicidins (CATHs), and Toll-like receptors (TLRs) in the isthmus and uterus of laying hens. Young and aged White Leghorn laying hens (35 and 130 wk old, respectively) were used. Total RNA and protein contents were isolated from the isthmic and uterine mucosae of these hens to examine the expression of TJ proteins, AvBD, and CATH genes and AvBD proteins by the real-time polymerase chain reaction and western blotting. The results showed that the mRNA expression of TJ proteins, namely zonula occludin 2 in the isthmus and occludin in the uterus, was higher in aged hens than in young hens. Expression of 2 AvBD genes in the isthmus and 4 AvBD genes in the uterus was higher in aged hens than in young hens. However, the expression of AvBD proteins 1 and 11 was not altered by aging. Expressions of CATH genes were not affected by aging in the isthmus or uterus. Expression of TLR genes was higher in aged hens than in young hens in the isthmus, while their expression in the uterus was not affected by aging. It can be concluded that aged hens have a higher potential ability to express TJ proteins and AvBDs for mucosal defense in the isthmic and uterine mucosae than in young hens.